THE HUBUNGAN BERAT TAS DENGAN NYERI PUNGGUNG BAWAH PADA ANAK SEKOLAH UMUR 12-14 TAHUN DI DENPASAR - Luh Ita Mahendrayani; Susy Purnawati; Nopi Andayani (Majalah Ilmiah Fisioterapi Indonesia, 2015)
Use of school bags with too much load will cause a variety of musculoskeletal problems such as low back pain. This study aims to determine the relation of bag weight with low back pain in student. Method: This is a cross-sectional study were conducted in May-June 2014. Selected sample in SDN 5 Panjer and SMPN 1 Denpasar using simple random sampling technique which were 123 students of class 6,7, and 8 randomized using a lottery number and obtained 62 samples. Results: Research subjects were aged 12 and 13 years old as much as 37.1%. Thirty-nine girls and 23 boys with an average body mass index category most were underweight as much as 43.5%. Students were carry school bags most severe category of bags are on ?15% of body weight as much as 46.8%. Low back pain experienced by most students who was bring a bag with the category of 6-13kg as much as 38.7%. Based on chi square test was get values of p = 0.001(p<0.05). Conclusion: That means there is a significant association between bag weight with back pain among elementary and junior high school student in SD Negeri 5 Panjer and SMP Negeri 1 Denpasar.